2017
DOI: 10.1103/physrevb.96.214436
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic structure of Ba(TiO)Cu4(PO4)4 probed using spherical neutron polarimetry

Abstract: The antiferromagnetic compound Ba(TiO)Cu4(PO4)4 contains square cupola of corner-sharing CuO4 plaquettes, which were proposed to form effective quadrupolar order. To identify the magnetic structure, we have performed spherical neutron polarimetry measurements. Based on symmetry analysis and careful measurements we conclude that the orientation of the Cu 2+ spins form a non-collinear in-out structure with spins approximately perpendicular to the CuO4 motif. Strong Dzyaloshinskii-Moriya interaction naturally len… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 18 publications
2
15
0
Order By: Relevance
“…Experimental configuration of the local field was compared to the calculated dipolar field for several magnetic arrangement of the copper magnetic moments. We found that the magnetic structure Γ 3 (1) determined by the previous neutron diffraction studies 1,6 is most consistent with the NMR data.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Experimental configuration of the local field was compared to the calculated dipolar field for several magnetic arrangement of the copper magnetic moments. We found that the magnetic structure Γ 3 (1) determined by the previous neutron diffraction studies 1,6 is most consistent with the NMR data.…”
Section: Discussionsupporting
confidence: 86%
“…The latter arrangement had smaller R-factor, thus being the most probable arrangement. Later Babkevich et al 6 confirmed the two possible structures using spherical neutron polarimetry, inclining by a discernible, albeit small advantage towards the Γ 3 (2) spin structure.…”
Section: Introductionmentioning
confidence: 95%
“…Two types of the square-cupola units (upward and downward) are present in the structure [see Fig. 1(b [2][3][4][5]. A huge anomaly in the temperaturedependent dielectric constant was observed at the Neél temperature T N 9.5 K in the magnetic field applied along the [100] and [110] directions.…”
Section: Introductionmentioning
confidence: 99%
“…In the present paper we focus our attention on the magnetization process and magnetocaloric effect of the spin-1/2 X X Z Heisenberg triangular and pentagonal cupola with an odd number of spins N = 9 and N = 15. In addition, we investigate the spin-1/2 X X Z Heisenberg square cupola with the total number of spins N = 12, for which several experimental realizations were found in the magnetic compounds Sr(TiO)Cu 4 (PO 4 ) 4 [42,43], Pb(TiO)Cu 4 (PO 4 ) 4 [44], Ba(TiO)Cu 4 (PO 4 ) 4 [45][46][47][48][49].…”
Section: Introductionmentioning
confidence: 99%